Cyberwarfare between the United States and China 2014 -2022: in Retrospect - Nadia Dian Ardita; Septyanto Galan Prakoso; Ferdian Ahya Al Putra; Arif Sulistiobudi; Randhi Satria (The Republic of Indonesia Defense University, 2023)
The development of security in the context of international politics and international relations has developed from time to time. Nowadays, the practice of security done by a country's government can be imbued with the advancement of technological innovation, dubbed cyber-influenced. Hence the term cyber-security is often used to indicate the association of information technology with security. The United States and China, as two competing big-power countries, also actively utilize cyber-security over the years. This article will describe the cyberwarfare between The United States and China, focusing from 2014 until 2022. A qualitative descriptive method is used, complemented by cyber security and state sovereignty concepts to analyze the case. Results indicate that both countries are involved in cyberwarfare based on defensive reasoning. The fact that both countries are referred to as great powers in international politics also complicates the case, as they have a high-tension nature of the relationship.